Magnetic Properties of Mixed Valence La(AgSr)MnO3 Manganites Obtained by Solid‐State Reaction Method. Issue 3 (6th December 2012) - Amano, M. E.; Betancourt, I.; Huerta, L.; Stevenson, J.
<x xml:space="preserve">Abstract</x> In this work, we present a systematic study on the effect of monovalent and divalent cation inclusion on the magnetic properties of the manganites series La0.80(Ag1−xSrx)0.20MnO3 (x = 0.0–1.0) synthesized by the solid‐state reaction method. The decreasing Sr:Ag proportion across the compositional series was verified by X‐ray photoelectron spectroscopy. Concerning magnetic properties, the hysteresis curves manifested an initial paramagnetic response at x = 0.0, followed by a progressive ferromagnetic behavior with an optimum Ag:Sr ratio at x = 0.75, for which an enhanced saturation magnetization of 51 Am2/kg and a Curie temperature of 336 K were recorded. Results are explained on the basis of the effect of the increasing unit cell volume on the double exchange interaction between magnetic Mn3+– Mn4+ atoms.